2010
DOI: 10.1108/17554171011091746
|View full text |Cite
|
Sign up to set email alerts
|

Islamic banking and customers' preferences: the case of the UK

Abstract: Purpose -Islamic banking is an increasingly important factor in the UK financial environment. With Islamic banks entering the industry in significant numbers -and competing directly with the incumbent "conventional" ones -the question of selection criteria of the banks' customers is of obvious interest. The purpose of this paper is to study the decision-making process of a sample of UK customers and the factors that may influence them. Design/methodology/approach -The paper uses a sample of 156 UK questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 11 publications
2
45
0
Order By: Relevance
“…Gerrard and Cunningham (1997) studied Singapore and Islamic banking by analyzing approaches of Muslim and non-Muslim customers. Mansour, Abdelhamid, Masood, and Niazi (2010) find in their survey of 156 United Kingdom located respondents that low service charges regardless of the demographic features and the religion of the respondent was the first criterion of the customers' criteria and it is followed by religious orientation.…”
Section: Malaysiamentioning
confidence: 99%
“…Gerrard and Cunningham (1997) studied Singapore and Islamic banking by analyzing approaches of Muslim and non-Muslim customers. Mansour, Abdelhamid, Masood, and Niazi (2010) find in their survey of 156 United Kingdom located respondents that low service charges regardless of the demographic features and the religion of the respondent was the first criterion of the customers' criteria and it is followed by religious orientation.…”
Section: Malaysiamentioning
confidence: 99%
“…There are number of studies focuses on both customers' awareness and satisfaction of product and services in Islamic financial system (see, Naser et al, 1999;Ahmad & Haron, 2002;Bley & Kuehn, 2003;Dusuki & Abdullah, 2007;Al-Ajmi et al, Adnan, 2010;Mansour et al, 2010). While, a few of studies have focused only on the consumers preferences to Islamic banking products (see, Gerrard & Cunningham, 1997;Metawa & Almoswawi, 1998;Bley & Kuehn, 2003;Rammal & Zurbruegg, 2006).…”
Section: Product and Servicesmentioning
confidence: 99%
“…Various studies (for example, Naser et al, 1999;Almossawi, 2001;Dusuki & Abdullah, 2007;Gait & Worthington, 2008;Mansour et al, 2010) have affirmed that the reputation as of the important contributors in the selection of Islamic banking among customers. It is in line with a takaful study, which found that majority of respondents chose reputation as their reason for choosing takaful operator (Bashir et al, 2011).…”
Section: Reputation and Recommendationmentioning
confidence: 99%
See 2 more Smart Citations